An Updated Checklist on Birds of Pallikaranai Marsh Land Chennai, Tamil Nadu, India - Thirunaranan, KVRK.; Samson, Arockianathan; Princy, Jabamalainathan Leona; Balaji, Navaneethasundaram; Ajith, Babu (Indian Forester, 2024)
The Pallikaranai Marsh Land is home to a diverse range of bird species in a transition zone that has been subject to disturbances. To ensure the preservation of the natural resources in the PML, it is recommended that human populations and constructions, including the garbage dump yard, be relocated outside of the area. Livestock grazing within the PML should also be prohibited, and efforts to eradicate Invasive Alien Species (IAS) should be implemented to further enhance bird conservation. The monitoring of avian fauna will be essential in promoting sustainable habitat improvement. With appropriate management and forest cover improvement programs, the PML has the potential to not only enhance the population of resident bird species but also attract migratory and vagrant species.